ZnO1−xSx Solid Solution as Potential Buffer Layer Materials for Cu2ZnSnS4‐Based Thin Film Solar Cells: Structural and Interfacial Properties. Issue 18 (20th May 2022) - Zhang, Yi‐Man; Jia, Zhan‐Ju; Zhao, Zong‐Yan; Zhao, Yun‐Kun
Abstract: The current low conversion efficiency of Cu2 ZnSnS4 (CZTS)‐based thin film solar cells is mainly blamed on the high carrier recombination via interface states at the absorber‐buffer. In this work, ZnO1− x S x solid solution is exploited as the potential buffer layer materials to solve this issue by using density functional theory calculations. With the varying of solid solubility, the lattice constant of ZnO1− x S x solid solution follows the first‐order Vegard's Law, while its bandgap follows the second‐order Vegard's Law. Based on the systematical analysis of crystal structure and electronic properties of ZnO1− x S x solid solution, ZnO0.375 S0.625 is screened as the optimal buffer layer material for CZTS‐based thin film solar cells, owing to the suitable bandgap (2.33 eV) and the smallest lattice mismatch (< 7%). The CZTS/ZnO0.375 S0.625 interface has less harmful interface state, small conduction band offset (− 0.02 eV) and band bending (− 0.23 eV). Moreover, its band alignment belongs to the staggered Type‐II heterojunction, and its built‐in electric field is in the same direction as the carrier migration, which is very favorable for the efficient separation and fast transfer of photogenerated carriers. Therefore, these interface features and effects of CZTS/ZnO0.375 S0.625 heterojunction can significantly boost the photovoltaic performance of CZTS‐based thin film solar cells. Abstract : The CZTS/ZnO0.375 S0.625 interface has less harmful interface state, small conduction band offset and band bending. Moreover, its band alignment belongs to the staggered Type‐II heterojunction, and its built‐in electric field is in the same direction as the carrier migration, which is very favorable for the efficient separation and fast transfer of photogenerated carriers.